Penerapan Metode Market Place Activity Untuk Meningkatkan Aktivitas dan Hasil Belajar Matematika pada Materi Penyajian Data - Hani Handayani; Williyanti Williyanti (Institut Nalanda, 2024)
This research was motivated by the low level of student activity and learning outcomes in mathematics learning, especially in data presentation material. One way that is expected to increase student activity and learning outcomes is by using the Market Place Activity method. The aim of this research is to describe the increase in student activity and learning outcomes through the application of the Market Place Activity learning method for class V students at SDN Margaluyu. The research method used is Classroom Action Research (PTK) which refers to the Kemmis and Mc model. Tagart, consists of two cycles. The instruments used include teacher performance observation sheets, activity observation sheets, and student learning outcomes. There are a total of 5 essay questions given in each cycle. The subjects of this research were 23 fifth grade students at SDN Margaluyu. Observation results showed an increase in student activity from 43.08% at the beginning to 86.13% in cycle II. The test results also showed an increase, with the percentage of student completion increasing from 22% at the beginning to 100% in the second cycle. Thus, the Market Place Activity method can increase activity and mathematics learning outcomes for class V at SDN Margaluyu, Sukasari District, Sumedang Regency for the 2023/2024 academic year.